Prebiotics and β-Glucan as gut modifier feed additives in modulation of growth performance, protein utilization status and dry matter and lactose digestibility in weanling pigs - Hayhoe, Mychal-Ann Natalie; Archbold, Tania; Wang, Qi; Yang, Xiaojian; Fan, Ming Z. (Frontiers in Animal Science, 2022)
There are growing concerns about the antimicrobial resistance to public health. Biological mechanisms of supplementing lactose for enhancing weanling pig growth are unclear. This study was prompted to determine effects of dietary supplementation of 3 prebiotics and β-glucan vs. a sub-therapeutic antibiotic on growth performance, whole-body protein utilization status and lactose digestibility in weanling pigs fed corn and soybean mean (SBM)-based diets. Six experimental diets were formulated with corn (40%), SBM (28%) and supplemented with dried whey powder (20%), and fish meal (9%) as the basal ingredients. Diet 1 (negative control, NC) contained no antibiotics and no supplemental prebiotics or β-glucan. Diet 2 (positive control, PC) contained an antibiotic premix (Lincomix 44 at 0.10%) in the basal diet. Diets 3 to 6 contained 0.75% of the three test prebiotics of retrograded resistant cornstarch (Diet 3), Fibersol-2 (a modified digestion-resistant maltodextrin, Diet 5) and inulin (Diet 6), and the viscous soluble fiber oat β-glucan (Diet 4), respectively. A total of 144 Yorkshire pigs at the age of 21 d were allocated to 12 floor pens with 6 pigs per pen, and fed one of the 6 diets for 21 d in 2 study blocks according to a completely randomized block design. There were no differences (P > 0.05) in ADG, ADFI, gain to feed ratio, plasma urea concentration, total tract DM and lactose digestibility and the calculated lactase digestive capacity among the diets. There were no differences (P > 0.05) in these endpoints between each of the four treatment diets and the NC or the PC diet. The total tract lactose digestibility was determined to be at 100%. The calculated lactase digestive capacity was about eight times the daily lactose intake and dietary supplementation of the prebiotics and the oat β-glucan at 0.75% did not significantly affect the major growth performance, whole-body protein utilization, as well as fecal DM and lactose digestibility in the weanling piglets . The growth-promoting effect associated with dietary supplemental lactose is likely due to the fact that lactose is a rapidly and highly digestible sugar rather than acting as an effective prebiotic in weanling pig nutrition.